Antimicrobial activity of nanostructured lipid carriers loaded with Melaleuca armillaris essential oil against Staphylococcus aureus sensitive and resistant to methicillin - Buldain, Daniel; Gortari Castillo, Lihuel; Marchetti, Laura; Buchamer, Andrea; Honor Irala, Federico; Islan, German; Mestorino, Nora (Frontiers in Nanotechnology, 2024)
IntroductionBovine mastitis is a major infectious disease affecting dairy cattle, impacting public health and milk industry profitability. Staphylococcus aureus is a contagious pathogen responsible for causing bovine subclinical mastitis. Its pathogenesis and antimicrobial resistance highlight the need for alternative treatments, being the nanoencapsulation of essential oils (EO) very promising.MethodsNanostructured lipid carriers (NLCs) containing 5% of Melaleuca armillaris EO were synthesized and characterized. Their physicochemical characteristics, antimicrobial activity against methicillin-resistant and sensitive S. aureus (MRSA and MSSA, respectively), and protective activity against polymorphonuclear cells were evaluated.ResultsNLC-EO nanoparticles were morphologically spherical and the mean size was around 190 nm, Polydispersity index (PdI) was 0.21 (±0.01), Z potential was −18.4 (±0.4) and EO encapsulation efficiency was 71.5%. Of this parameters Z potential was the only which changed after 6 months of storage at four°C, turning into a more negative value of −31.6 (±1.9). NLC-EO showed a biphasic behavior with a fast initial release during the first 6 h, followed by a slow phase for at least 72 h. Free and nanoencapsulated EO had a minimum inhibitory concentration (MIC90) of 6.25 μL/mL; however, free EO had a minimum inhibitory concentrations of biofilm formation (MICB90) of 3.12 μL/mL and for EO nanoencapsulated was 6.25 μL/mL. Minimum inhibitory concentrations of biofilm formation and eradication (MECB90) were 12.5 μL/mL and 6.25 μL/mL for the nanoencapsulated EO and free EO, respectively. Empty NLC inhibited biofilm formation, but not planktonic growth or eradicated preformed biofilms.DiscussionThe EO was efficiently encapsulated and released from NLC, and its antimicrobial activity against MRSA and MSSA was high. Neutrophil viability was higher when EO was encapsulated, being an important result for future experiments evaluating intracellular EO activity, where Staphylococcus aureus survives and evades poorly penetrating antibiotics activity.